Hydrodynamics of trickle-bed reactors: experiments and CFD modeling - Gunjal, P. R.; Kashid, M. N.; Ranade, V. V.; Chaudhari, Raghunath V. (Industrial & Engineering Chemistry Research, 2005)
{Hydrodynamics of trickle-bed reactors involve complex interactions of gas and liquid phases with packed solids. Such complex interactions manifest in different flow regimes occurring in trickle-bed reactors. Knowledge of prevailing flow regime, pressure drop, and liquid holdup is essential for design and performance evaluation of the reactor. Detailed knowledge of fluid dynamics is essential for ``a priory'' predictions as well as for interpretation of available data. In this study, we have used wall pressure fluctuation measurements to identify prevailing flow regime in trickle beds. Experiments were carried out on two scales of columns (of diameter 10 cm and 20 cm) with two sets of particles (3 min and 6 mm diameter spherical particles). Effects of prewetted and unwetted bed conditions on pressure drop and liquid holdup were reported for a range of operating conditions (V-G = 0.22-0.44 kg/m(2)s

Hydrodynamics and liquid phase residence time distribution in mesh microreactor - Kulkarni, A. A.; Gorasia, A. K.; Ranade, V. V. (Chemical Engineering Science, 2007)
This paper is focused on the experimental analysis of residence time distribution and phase hold-up in a mesh microreactor. A microreactor, where a finely weaved mesh is sandwiched between two flat plates with specific inlets for gas and liquid, is proposed. The microvolumes formed upon sandwiching the mesh are totally connected and thus it yields a view of several interconnected microvolumes. This system is easy to build and does not need precision micromachining. A high-speed photographic analysis yielded the phase distribution for different mesh types over a wide range of operating gas and liquid flow rates. The RTD was studied by measuring the liquid phase conductivity at the outlet of the reactor. Channeling prevailed for mesh with smaller open area. The ADEM was used for fitting the tracer curves with tailing ends. The RTD and the image analysis for all the mesh types showed hysteresis when the gas flow rate was maintained constant and the liquid flow rate was gradually increased and then decreased. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: hydrodynamics; hysteresis; image analysis; microreactor; residence time distribution